2018
DOI: 10.11648/j.sjbm.20180601.11
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Exploitative and Explorative Learning on the Relationship Between Job Embeddedness and Innovative Work Behavior

Abstract: It is the people and not the organizations that innovate and make a difference. Research has shown that thinking and implementing novel and useful ideas is one of the most difficult tasks for the employees and among many factors contributing to foster it, the role of job embeddedness has received little attention. This study draws on Organizational Ambidexterity Learning theory and Job Embeddedness Theory to conceptualize and confirm the relationship between job embeddedness, innovative work behaviour, and emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Fourth, the direct promotion effect of job embeddedness on voice behaviour had been confirmed in this study, which was also stated in Hypothesis 4; that is, employees with high job embeddedness had more active voice behaviour. Higher job embeddedness indicated that employees had a higher sense of belonging to the organisation, which would also lead to more positive work behaviours, including voice behaviour (Bibi & Jadoon, 2018). With the enhancement of job embeddedness, employees tended to invest more energy in their work to repay the organisation and may put forward reasonable suggestions and point out the existing problems (Ng & Feldman, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the direct promotion effect of job embeddedness on voice behaviour had been confirmed in this study, which was also stated in Hypothesis 4; that is, employees with high job embeddedness had more active voice behaviour. Higher job embeddedness indicated that employees had a higher sense of belonging to the organisation, which would also lead to more positive work behaviours, including voice behaviour (Bibi & Jadoon, 2018). With the enhancement of job embeddedness, employees tended to invest more energy in their work to repay the organisation and may put forward reasonable suggestions and point out the existing problems (Ng & Feldman, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous research (Allen, 2006;Holtom et al, 2006;Crossley et al, 2007;Robinson et al, 2014;Bibi and Jadoon, 2018;Coetzer et al, 2017) argued that higher levels of employees' feelings regarding job embeddedness are positively associated with higher levels of organisational commitment, while the association between job embeddedness and intentions to leave is found to be negative. Job embeddedness framework provided by Mitchell et al (2001) and Robinson et al (2014) suggested that when an employee's own values, career goals and future plans are consistent with the job demands, they experience an alignment with the larger corporate culture and feel suited with the surrounding environment and community.…”
Section: Job Embeddedness Organisational Commitment and Intention To Leavementioning
confidence: 97%
“…Furthermore, some studies have investigated the different influences emerged as a result of some organisational and community sub-factors (Lee et al, 2004;Allen, 2006;Wheeler et al, 2010;Bibi and Jadoon, 2018). These studies dealt with the first-order sub-variables of job embeddedness as equally weighted factors and compiled them to shape composites.…”
Section: Job Embeddedness Organisational Commitment and Intention To Leavementioning
confidence: 99%
“…Exploitative learning is the direct use and transformation of existing knowledge and skills. It is an extension of the existing capabilities and paradigms of firms and improves the operating efficiency of firms on the current basis (Bibi and Jadoon, 2018). According to the resource-based view, firms deeply analyze the practical difficulties they face in the process of development and make full use of existing knowledge resources to achieve the purpose of improving the innovation ability of firms (Grant, 1991;Caldeira and Ward, 2003;Popovi c et al, 2018).…”
Section: 2mentioning
confidence: 99%